A POLÍTICA SOCIAL DE EDUCAÇÃO SUPERIOR ANTE A PROPOSTA DE REFORMA DO ESTADO BRASILEIRO DE BRESSER PEREIRA - Débora Spotorno Moreira Machado Ferreira (Revista de Políticas Públicas, 2010)
This article is part of the reflections over the following topic: Higher Education Policies in Lula ́s Government and its implications for Social Worker ́s Professional Formation. The understanding of what is presented in this assay is based on the theoreticial-methodological Marx ́s social critical theory, seeking, from a reality phenomenon - its appearance and legalities - to get to know its ́ essence.